Cost volume profit analysis and profit planning in manufacturing SMEs in Nigeria / Kenneth Enoch Okpala and Chimsunum Osanebi - Okpala, Kenneth Enoch; Osanebi, Chimsunum (Accounting Research Institute (ARI), 2020)
The manufacturing SMEs encounter many problems, one of which is the inability to earn a sustainable profit for continuity. Inadequate profitability is one the factors responsible for the early death of SMEs in Sub Sahara, Africa. This study examined the usage of the cost volume profit technique on profit planning in manufacturing SMEs as a means to solve the problem. A cross sectional survey research design was adopted, and the study sample population from snowballing consisted of 50 manufacturing SMEs with 1048 senior staff. A questionnaire was used to elicit the respondents' opinions, and 714 useable copies of the survey were returned. Descriptive statistics, Pearson product-moment correlation, and Regression analysis methods were used for data analysis. The study concluded that cost volume profit analysis has a positive and statistically significant impact on profit planning (β=.645, P=.00<.05). The study recommends that the management of manufacturing SMEs should employ and retain high-caliber accountants and restructure their management team for effectiveness. The decisionmaking process should be streamlined for planning efficiency, and top management should support the cost volume profit analysis model to aid adequate implementation and results.